Conceptual design and thermodynamic investigation of novel energy and fuel generation systems from municipal waste coupled with carbon capture and storage - Qurrotin Ayunina Maulida Okta Arifianti; Stavros Michailos; Maria Fernanda Rojas Michaga; Karim Rabea; Kevin J Hughes; Lin Ma; Derek Ingham; Mohamed Pourkashanian (Energy Nexus)
Waste generation and energy demand are increasing and both require innovative energy symbiosis strategies to meet climate targets. Traditional waste-to-energy processes rely on incineration, but more efficient and sustainable solutions are needed. The aim of the study is to investigate for the first time the feasibility of generating cooling, heating, power (CCHP), and liquid biomethane from plastics and food waste integrated with carbon capture and storage (CCS). The system, modelled in Aspen Plus, consists of a plasma gasifier (PG), anaerobic digester (AD), combined cycle gas turbine (CCGT), absorption refrigeration cooler (ARC), and biomethane liquefier. Two scenarios were analyzed: (1) a standalone CCHP system and (2) its integration with liquid biomethane production. Each scenario includes a baseline (without CCS), pre-combustion CCS, and post-combustion CCS, both with a 95% CO₂ capture fraction. Utilising 5 kg/s of plastic and 13.97 kg/s of food waste, the system generates net power (29.76–85.67 MW), cooling (2.72–4.04 MW), heating (13.99–27.87 MW), and 43.26 MW of liquid biomethane. The highest energy and exergy efficiencies achieved are 49.44% and 41.20%, with carbon emissions ranging from 0.008 to 0.247 kgCO₂/kg waste. The findings of this novel study highlight the potential of integrating several energy systems for an effective waste management strategy that can contribute to the provision of several energy vectors while the inclusion of CCS ensures that significant emission reduction can be attained.